The Problem of Zombie Businesses in the Global Economy - Kirill Kurilov; Anastasia Kurilova (Communications of International Proceedings, 2020)
The current situation in the world economy is characterized by instability and lack of progressive movement towards social well-being. A sharp decline in interest rates and concessional government financing of large socially significant enterprises led to the emergence of enterprises that are highly likely to be unable to pay off their debts. The COVID-19 pandemic has led to an increase in the number of zombie businesses and an increase in their debt. It should also be noted the emergence in the world economy of states that are similar in their characteristics to zombie enterprises. The main distinguishing feature of these countries is the inability to pay off their debts through the economic activities of their economies, since the debt of these countries exceeds their annual GDP. At the same time, due to securitization, zombie enterprises and zombie countries issue various financial assets, including bonds, which are bought by solvent and well-known companies such as Apple. In this regard, it is relevant to search for a model for the distribution of zombie assets of economic entities.
Keywords: zombie enterprises; zombie countries; financial instruments; bonds; junk bonds; GDP; infection model